Bentuk-bentuk Kekerasan yang Dilakukan Orang Tua pada Anak di RW II Kelurahan Olo Nanggalo Kota Padang - Arisna, Ranial (Bimbingan dan Konseling, 2014)
The problem that research on based fenomena, researcher find in field there are, parents yet fully basic privacy children and educate children with do physical and psychis abuse. The purpose of the research there are to describe: 1) forms phsyical abuse that do parents to children, 2) forms psychis abuse do parents to children. The research is quantitative descriptive. The result of problem there are: 1) forms of physical abuse that do parents to children 65% in chategory very much, 2) forms of psychis abuse that do parents to children 45% in chategory very much.